Reading about Nymphs and Roman Soldiers with and without Frazer - Köster, Isabel (New Age Movements, Occultism, and Spiritualism Research Library, 2023)
This talk explores the usefulness and pitfalls of using Frazer’s theories to interpret inscriptions that refer to dedications made by (or on behalf of) Roman soldiers to nymphs. Starting with an overview in The Golden Bough, Frazer's descriptions of water and woodland spirits, collectively known as nymphs, are explored. Four inscriptions are discussed from Roman Britain that are representative of these texts: an altar for the nymphs dedicated by a group of soldiers (RIB 460= CIL 7.171); a dedication to the nymph Brigantia and the emperors made by a high ranking officer (RIB 2066=CIL 7.875); a dedication to the nymph Coventina made by a soldier for himself and his family (RIB 1526); a dedication made on behalf of a soldier by his wife (RIB 1228= CIL 7.998). Additional Authors: Shaking the Tree, Breaking the Bough: Frazer's Golden Bough at 100 (Conference); Tully, Caroline Jane; Budin, Stephanie Lynn; University of Melbourne;
1 video file. ms150-40-017_koster-isabel_nymphs_2023-02-11.mp4 .mp4 314.51 MB 329,786,684
Keywords: Nymphs (Greek deities); Brigit (Celtic deity); Coventina (Romano-British goddess); Offerings; Altars; Romans--Great Britain; Soldiers--Roman--Religious life--Great Britain; Frazer, James George, 1854-1941. Golden bough; Conference papers and proceedings; Literary criticism